1988
DOI: 10.1139/z88-312
|View full text |Cite
|
Sign up to set email alerts
|

Infraciliature, système myonémique, argyrome et bipartition de l'Astylozoon pyriforme (Ciliophora, Peritrichida)

Abstract: Astylozoon pyriforme is a stalkless peritrich whose ciliature is restricted to the oral region and reduced to a few aboral bristles at the posterior pole. As in other peritrichs, the infraciliature is located in two zones, oral (peristome and infundibulum) and aboral (trochal band and scopule). We also observed an epistomial membrane located in the region where the peristomial infraciliature begins, to the right of the haplokinety. The myonemic system of this ciliate has three parts: an oral myonemic ring, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…86; Guinea et al. ). All these authors indicated that all three rows will elongate toward the cytostome except Wu et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…86; Guinea et al. ). All these authors indicated that all three rows will elongate toward the cytostome except Wu et al.…”
Section: Discussionmentioning
confidence: 99%
“…118, 119), the kinetosomes of the Gk proliferate to form a relatively elongate GA that extends toward the cytostome (Esteban and Fernández‐Galiano ; Guinea et al. ; Lom ; Sola et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on the peritrich myoneme system have been carried out on a variety of taxa, including: Opisthonecta spp., Carchesium polypinum, Epicarchesium granulatum, Epistylis plicatilis, Heteropolaria colisarum, Vorticella spp., Hastatella spp., and Astylozoon spp. (Wang, 1950;Bradbury, 1965;Zagon, 1970;Foissner, 1977;Foissner and Schubert, 1977;Fernandez-Leborans, 1982;Sola et al, 1985;Guinea and Fernandez-Galiano, 1987;Guinea et al, 1988;Fernandez-Galiano and Carrascosa, 1989;Foissner et al, 1992;Leitner and Foissner, 1997). and is now routinely included in studies of peritrich morphology (Foissner et al, 1992, and references therein).…”
mentioning
confidence: 99%